Variation of lipid and fatty acid compositions in Thai Perilla seeds grown at different locations - Sirithon Siriamornpun (2018)
Perilla or Nga-Kee-Mon (Perilla frutescens) seed has long been known as a rich source of α-linolenic acid (18:3, n-3). It is widely cultivated throughout Thailand. However, there are no data on the variation of lipid and fatty acid compositions among crops from different regions. The aim of this study was to examine the compositions of lipids and fatty acids in Thai perilla seed grown at different locations. Two different perilla seeds were harvested from Maehongsorn and Chiang Mai districts, and one commercial perilla was purchased from local market. Seeds were ground, lipid was extracted with chloroform: methanol (2:1, v/v) and its composition determined by Iatroscan (TLC/FID). Fatty acid composition was analyzed with GLC using standard methods. Lipid content was between 34-36% (w/w). Triacylglycerol was a predominant lipid in perilla seed (97% of total lipids), and a minor component was phytosterol (3% of total lipids). The ratio of saturates: monounsaturates: polyunsaturates was approximately 1: 1: 8. Most predominant fatty acid was α-linolenic acid (18:3, n-3) (55-60% of total fatty acid). Seeds from Maehongsorn district had the highest concentration of α-linolenic acid, and commercial perilla had the lowest (P<0.05). Other two predominant fatty acids were linoleic acid (18:2, n-6) (18-22% of total fatty acid) and oleic acid (18:1) (11-13% of total fatty acid). The results showed that the compositions of lipids and fatty acids in Thai perilla seeds varied significantly among samples from different locations.